Ngelungah Ceremony In Pitra Yadnya - Ni Ketut Kantriani (Kamaya: Jurnal Ilmu Agama, 2021)
In daily life, Hindus always carry out religious activities known as yajñas. It is carried out based on the objectives of Hinduism as stated in the Vedic scriptures, namely “moksartham jagadhita ya ca iti dharma” which means that dharma or religion is to reach moksa (jagadhita). Moksa is also known as mukti, which means achieving spiritual freedom or lasting spiritual happiness. Jagadhita is also known as bhukti, which means for the prosperity of people’s lives and the State. Pitru yajña ceremony is a form of yajña conducted by Hindus in Bali. In general, Pitra Yajña is classified into three, namely 1) Mendem Sawa (corpse), 2) Ngaben, and 3) Nelungah. Ngelungah is a form of Pitra Yajña that is conducted specifically for babies who die after kepus puser and before teething. However, in reality, Hindu religious activities in Bali that Ngelungah is carried out not based on literary instructions because Ngelungah ceremony is carried out every time a baby dies and there is also a ceremony for babies due to miscarriage. Ngelungah is based on people's belief that based on the family's situation in the form of calamity, such as a sick that cannot be healed medically.